A randomized trial comparing safety, immunogenicity and efficacy of self-amplifying mRNA and adenovirus-vector COVID-19 vaccines - Nhan Thi Ho; Steve G. Hughes; Rose Sekulovich; Van Thanh Ta; Thuong Vu Nguyen; Anh Thi Van Pham; Quang Chan Luong; Ly Thi Le Tran; Anh Thi Van Luu; Anh Ngoc Nguyen; Ha Thai Pham; Van Thu Nguyen; et al. (npj Vaccines, 2024)
Abstract This phase 3 trial compared safety, tolerability, immunogenicity and efficacy of the self-amplifying mRNA COVID-19 vaccine, ARCT-154, with ChAdOx1-S adenovirus-vector vaccine. In four centers in Vietnam adult participants aged 18‒85 years were randomly assigned to receive two doses, 28 days apart, of either ARCT-154 (n = 1186) or ChAdOx1-S (n = 1180). Both vaccines were well tolerated with similar safety and reactogenicity profiles consisting of mainly mild-to-moderate solicited adverse events and few related serious adverse events. Higher neutralizing antibody responses persisting to one-year post-vaccination after ARCT-154 compared with ChAdOx1-S were associated with a generally higher efficacy against COVID-19. In an exploratory analysis relative vaccine efficacy of ARCT-154 vs. ChAdOx1-S against any COVID-19 from Day 36 to Day 394 was 19.8% (95% CI: 4.0–33.0). Self-amplifying mRNA vaccine offers potential immunological advantages in terms of immunogenicity and efficacy over adenovirus-vector vaccine without compromising safety.